"A New Vocation before Me": Frederick Douglass's Post-Civil War Lyceum Career. Issue 3 (3rd July 2018) - McKivigan, John R.
ABSTRACT: This article examines the oratorical strategies adopted by Frederick Douglass in the late 1860s and early 1870s when he joined the ranks of professional lyceum speakers. Douglass's speaking shifted away from the long-established topics of slavery and civil rights to appeal to a broader audience. Douglass also shifted from a spontaneous speaking style, honed in years of abolitionist campaigning, to rely upon written texts prepared in advance and delivered repeatedly. A close analysis of those lyceum addresses, newspaper reports of their delivery, and Douglass's personal correspondence reveal that he retained many elements of his older performance style and facilely adapted his topic, sometimes in mid-lecture, to suit many audiences' demand to hear him address the "race question."